Brain health - McKay, Sarah (Neuroscientist) (--For dummies., 2025)
"The brain is your hardest-working organ. Brain health for dummies shows you how to support its many functions, so it can keep thriving for years to come. Brain health is important for your mood and mental health, performance at school and work, and your well-being as you age. With the simple strategies inside, you can keep your brain in top shape and lessen your chance of decline later in life. This book explains the science behind brain health and gives you advice you can use as you become your own brain health coach"--